Book Reviews (Blackfriars, 1932)
BOOK REVIEWS in this articles: Chaucer. By G. K. Chesterton. René Guénon traces a secret language in the works of Dante, and proclaims the great Florentine to be an initiate. Summa Theolociae Mforalis: Ad Mentem D. Thomae Et Ad Normam Juris Novi. By Benedict Henry Merkelbach, O.P. Vol. I; de Principiis et Virtutibus theologicis The Dominican Missal. In Latin and English. ST. Germaine Of The Wolf Country. By Henri Ghéon. Translated by F. J. Sheed, and illustrated by Marigold Hunt. Les Fondements Spirituels De La Vie. Par Vladimir Soloviev. Traduction du russe par le R. P. Georges Tzebricow avec la collaboration de l'Abbé A. Martin. The King's Book; or, A Necessary Doctrine and Erudition for any Christian Man, 1543. With an Intrduction by T. A. Lacey. Preface by Viscount Halifax. Edition reprinted by photographic process from Bishop Charles Lloye's edition of Formularies of Faith put forth by Authority during the reign of Henry VIII, Oxford, 1825. The Little Marie-José. By Elinor M. Brent-Dyer. Calvin's First Psalter. A Medieval Carol Book; and Gilbert And Sandys' Christmas Carols. Chrestomathia Bernardina Ex Operibus S. Bernardi. Compilatore P. Dr. Emerico Piszter, S.O.Cist. The Renewed Church Of The United Brethren, 1722—2930. By William George Addison, M.A., B.D., Ph.D. Marriage. From the French of Raoul Plus, S.J. Leaves From Life. By Dr. E. J. Dillon. Life Of The Venerable Anne Of Jesus, Companion Of St. Teresa Of Avila. By a Sister of Notre Dame de Namur. Maria Teresa Countess Ledochowska, Foundress Of The Sodality Of St. Peter Claver. By Valeria Bielak. Translated from the Italian. The Bliss Of The Way: A Bedside Book for the Tramp. By Cecily Hallack. Consummata (Marie-Antoinette De Genser), Her Life And Letters. Translated from the French of Raoul Plus, S.J., by George Baker. De Matrimoniis Mixtis Eorumque Remediis. By Fr. Francis Ter Haar, C.SS.R. The Seven Niches. By Egerton Clarke. The Lives Of The Saints. By Alban Butler. A new edition, corrected, amplified and edited by Herbert Thurston, S.J., and Donald Attwater. Vol. vii, July. Magnificat. By René Bazin. The Irish Way. Edited by F. J. Sheed. Happy Endings. By Noel Macdonald Wilby. The Oxford Movement: by the Rev. Henry Browne, S.J.; pp. 40. Christ the King: by the Rev. John O'Connor; pp. 20. The New Papal state: by Benedict Williamson; pp. 28. St. Bernardine Of Siena: by the Rev. Dominic Devas, O.F.M.; pp. 32. Ludovico Necchi, a Leader of Catholic Action: by Mgr. Olgiati; translated from the Italian by the Rev. Henry; Louis Hughes, B.A., D.Litt.; pp. 72. The Order Of Standing And Kneeling At Mass And Office;